Temporal variation of biomass and productivity of Thalassia testudinum(Hydrocharitaceae) in Venezuela, Southern Caribbean - Pérez, Daisy (2006)
Annual biomass and productivity of Thalassia testudinum were determined during a year at a seagrass bed located in the Parque Nacional Morrocoy, Venezuela. Leaf, rhizome and root biomass were determined monthly, together with short-shoot density, from February 1992 to January 1993, from nine replicated core samples. Productivity was measured using the methodology by Zieman (1974) with minor modifications, and leaf turnover rate was calculated. Leaf biomass values ranged between 101.73 dry g m-2 in February and 178.11 dry g m-2 in August. Productivity ranged from 1.69 dry g m-2 d-1 in April and October to 3.30 dry g m-2 d-1 in July, showing two annual peaks: one in July and one in March. The leaf turnover rate showed the highest value in June (2.41% d-1) and the lowest in May (1.23% d-1). Sampling time differences in leaf biomass, productivity and turnover rate were statistically significant. Short-shoot density values varied between 811.10 shoots m-2 in April and 1226.08 shoots m-2 in December, but the differences were not significant along the year. These results indicated seasonal trends for leaf biomass, productivity and turnover rate of T. testudinum in the Southern Caribbean (latitude 10°N).